Damage zones induced by in situ stress unloading during excavation of diversion tunnels for the Jinping II hydropower project - Fan, Y.; Zheng, J. W.; Cui, X. Z.; Leng, Z. D.; Wang, F.; Lv, C. C. (Bulletin of engineering geology and the environment, 2021)
During the excavation of deep tunnels with high in situ stress, the stress unloading path caused by the rock mass excavation has important influences on the formation of the EDZ (excavation damage zone). In this study, the project background of the Jinping II diversion tunnels was firstly introduced. Then, the influences of stress unloading path induced by blasting excavation and tunnel boring machine (TBM) excavation on the EDZ were analyzed based on the acoustic data. Finally, the effects for different unloading paths of in situ stress induced by different excavation methods on the EDZ were studied by theoretical calculation and numerical simulation. The results show that compared with the quasi-static unloading, the transient unloading amplifies the effects of radial stress unloading and the tangential stress loading in surrounding rock masses. The EDZ depths of the blasting excavation tunnel are about 1.0 m greater than those of the TBM excavation tunnel. Moreover, the depths of the low-velocity band of the blasting excavation tunnel account for more than 50% of the total EDZ depths, while the depths of the low-velocity band of the TBM excavation tunnel account for about 30% of the total EDZ depths. The distribution of the low-velocity band along the excavation contour is closely related to the secondary stress field, indicating that the transient unloading of in situ stress is one of the important causes of the low-velocity band. After considering the post-peak mechanical properties of marble, the EDZ extents induced by different excavation methods can be estimated through numerical simulation.